Host SUMOylation in bacterial infections and immune defense mechanisms - Xu, Yuhua; Ma, Xi; Wu, Zhifeng; Huang, Ruitong; Liao, Chenhua; Huang, Di; Tang, Yujun; Zhu, Chengbin; Wang, Yaqi; Zhang, Siyuan; Liu, Peng; Peng, Jiaofeng (Frontiers in Microbiology, 2025)
SUMOylation, the covalent attachment of small ubiquitin-like modifier proteins (SUMO) to lysine residues of target substrates, has emerged as a crucial post-translational modification regulating various cellular processes. Recent studies have revealed that SUMOylation also plays significant roles in host-pathogen interactions during bacterial infections. On the one hand, SUMOylation can modulate host innate immune responses, such as inflammatory signaling and autophagy, to defend against invading bacteria. On the other hand, certain bacterial pathogens have evolved strategies to exploit or manipulate the host SUMOylation machinery to promote their survival and replication. Some bacterial effector proteins directly target host SUMO enzymes or SUMO-conjugated substrates to disrupt host defense mechanisms. This review summarizes the current understanding of the complex interplay between SUMOylation and bacterial infection, highlighting the dual roles of SUMOylation in host defense and bacterial pathogenesis. We discuss the mechanisms by which SUMOylation regulates host immune responses against bacterial infection and how bacterial pathogens hijack host SUMOylation for their own benefit. Moreover, we explore the potential of targeting SUMOylation as a novel therapeutic strategy for combating bacterial infections. Further research into the intricate relationship between SUMOylation and bacterial infection may provide valuable insights for developing innovative anti-infective therapies.